Comparison of age-related morphological changes in the masseter muscles of senescence-accelerated mouse (SAM). Issue 1 (January 2018) - Hoshino, Teruhide; Yamamoto, Masahito; Kasahara, Kiyohiro; Katakura, Akira
Abstract: Objective: Age-related morphological changes in the perioral muscles are still garnering attention today. We planned an experiment using a senescence-accelerated mouse (SAM) to compare age-related morphological changes in the masseter muscle in young and old mice. The masseter muscle in elderly mice (40 -week- old) of SAM-prone 8 (SAMP8) mice has been found to demonstrate greater muscle fiber atrophy than that in a control group of SAM-resistant 1(SAMR1) mice. In the present study, in order to assess age-related morphological changes in the masseter muscles of SAMP8 mice, we compared three groups of mice: young mice (12 -week- old), elderly mice (40 -week- old), and later-stage elderly mice (55 -week- old). Materials and methods: The body weight, the masseter muscle wet weight and the serum albumin levels of each stages in SAMP8 mice were measured. Also, SAMR1 mice were measured as control. Frozen sections of sampled muscles were prepared and dyed with Hematoxylin-eosin (H-E) and immunohistochemical staining. Results: The mean cross-sectional area of muscle fibers decreased from 12- week- old to 40- week-old and from 12- week- old to 55- week- old. Immunohistochemical staining showed that the percentage(%) of MyHC-IIa increased from 12- week- old to 55- week- old, whereas that of MyHC-IIb decreased from 12- week- old to 55- week- old and 40- week- old to 55- week- old. Conclusions: In the present study, it showed that atrophy of the masseter muscle had occurred by 40- week- old and that there were additional subsequent changes in contraction characteristics.